Development of a rapid efficient solid-phase microextraction: An overhead rotating flat surface sorbent based 3-D graphene oxide/ lanthanum nanoparticles @ Ni foam for separation and determination of sulfonamides in animal-based food products. (30th March 2022) - Shirani, Mahboube; Parandi, Ehsan; Nodeh, Hamid Rashidi; Akbari-adergani, Behrouz; Shahdadi, Fatemeh
Highlights: Rotating flat surface solid-phase microextraction (RFS-SPME) as a novel method. 3-D graphene oxide/ lanthanum nanoparticles @ Ni foam as an efficient sorbent. Combination of RFS-SPME with GO-La NPs @ Ni foam for separation of sulfonamides. Successful application of the method in animal-based food products as complex matrixes. Abstract: In this study, an overhead rotating flat surface sorbent based solid-phase microextraction was developed as a rapid and efficient method for simultaneous separation and determination of sulfonamides in animal based-food products. 3D graphene oxide/ lanthanum nanoparticles @ Ni foam was introduced as a novel selective sorbent. SEM-EDX and FT-IR techniques were applied for characterization of the sorbent. At optimum conditions, the linear ranges of 0.4–700.0 (µg L -1 ), 0.3–900.0 (µg L -1 ), and 0.25–500 (µg L -1 ) and the enrichment factors of 606.8, 604.3, 608.9 were obtained for SDZ, SMX, and SMZ, respectively. The LOD (S/N = 3) of 0.14, 0.11, 0.08 (µg L -1 ) were achieved for SDZ, SMX, and SMZ, respectively. The intra-day and inter-day precision (%) (five days, n = 7) for the concentration of 100 µg L -1 were less than 4.3 and 3.8, respectively. The recoveries over 90.0 % revealed high capability of the method for utilization in complex matrixes.